Conscious and nonconscious discrimination of facial expressions - Herba, C; Heining, M; Young, A; Browning, M; al., E (Taylor and Francis, 2007)
Abrupt discontinuities in recognizing categories of emotion are found for the labelling of consciously perceived facial expressions. This has been taken to imply that, at a conscious level, we perceive facial expressions categorically. We investigated whether the abrupt discontinuities found in categorization for conscious recognition would be replaced by a graded transition for subthreshold stimuli. Fifteen volunteers participated in two experiments, in which participants viewed faces morphed from 100% fear to 100% disgust along seven increments. In Experiment A, target faces were presented for 30 ms, in Experiment B for 170 ms. Participants made two-alternative forced-choice decisions between fear and disgust. Results for the 30 ms presentation time indicated a significant linear trend between degree of morphing and classification of the images. Results for 170 ms presentation time followed the higher order function found in studies of categorical perception. These results provide preliminary evidence for separate processes underlying conscious and nonconscious perception of facial expressions of emotion.